Ответы и объяснения

  • Участник Знаний
2015-07-06T10:54:31+03:00
x^4-2x^3-18x^2-6x+9=0
  Выносим общий множитель:
(x^4+9)-2x(x^2+3)-18x^2=0\\ (x^4+6x^2+9-6x^2)-2x(x^2+3)-18x^2=0\\ (x^2+3)^2-6x^2-2x(x^2+3)-18x^2=0\\ (x^2+3)^2-2x(x^2+3)-24x^2=0|:x^2\\ (x^2+3)^2:x^2-2(x^2+3):x-24=0
 Пусть (x^2+3):x=t, тогда получаем
t^2-2t-24=0
 По т. Виета: t_1=-4;\,\,\,\, t_2=6
Возвращаемся к замене
(x^2+3):x=-4|\cdot x\\ x^2+3=-4x\\ x^2+4x+3=0
 По т. Виета: x_1=-3;\,\,\,\, x_2=-1

(x^2+3):x=6|\cdot x\\ x^2-6x+3=0
 Находим дискриминант
D=b^2-4ac=(-6)^2-4\cdot 1\cdot 3=24;\,\, \sqrt{D} =2 \sqrt{6}
x_3_,_4= \frac{6\pm2 \sqrt{6}}{2} =3\pm \sqrt{6}

Ответ: -3;\,-1;\,3\pm \sqrt{6}